Building and developing agent based modelling for higher order logic in neuro symbolic integration. - Sathasivam, Saratha (Universiti Sains Malaysia, 2015)
We will develop agent based modelling (ABM) for doing logic programming and Reverse Analysis method in doing higher order logic programming. Later, we will build another ABM for the upgraded method (integrating Boltzmann machine and Modify Activation Function). Agent-based Modelling (ABM) which also called individual-based modelling is a new computational modelling paradigm which is an analyzing systems that representing the 'agents' that involving and simulating of their interactions. We will test ABM for this upgraded method (higher order logic programming, Hopfield network, Boltzmann machine and activation function in some real life and simulated data sets. We are going to test this method on some constraint optimization problems.